THE ROLE OF MOSQUES IN COMMUNITY ECONOMIC RECOVERY DURING THE COVID-19 PANDEMIC - Rizki, Ikhsanul; Zulaikha, Siti (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: The mosque has many roles and functions, one of which is economic empowerment. As a place for economic empowerment, mosques must play a role in the economic recovery of people who have experienced adversity during the Covid-19 pandemic. This study aims to find out how is the role of mosques in the community's economy during the Covid-19 pandemic. Methods: The research used a qualitative method with a case study approach. Results: The results of the study show that the Jogokariyan Mosque has succeeded in recovering the community's economy during the pandemic with various programs. These programs are given to the poor in the form of basic necessities and given to MSME actors by holding people's markets; mosques help market participants by providing Al-Qardh loans, providing education about entrepreneurship, and providing free shopping vouchers for the poor and mosque congregations to stimulate sales of people's market participants. Conclusion and suggestion: Mosque administrators must work better in managing their mosques so that mosques can maximize their roles and functions and not only be used as places of worship. The role and function of the mosque can solve all the problems of the congregation.